2018
DOI: 10.1016/j.celrep.2018.04.106
|View full text |Cite
|
Sign up to set email alerts
|

A Batf3/Nlrp3/IL-18 Axis Promotes Natural Killer Cell IL-10 Production during Listeria monocytogenes Infection

Abstract: SUMMARYThe bacterial pathogen Listeria monocytogenes (Lm) capitalizes on natural killer (NK) cell production of regulatory interleukin (IL)-10 to establish severe systemic infections. Here, we identify regulators of this IL-10 secretion. We show that IL-18 signals to NK cells license their ability to produce IL-10. IL-18 acts independent of IL-12 and STAT4, which co-stimulate IFNγ secretion. Dendritic cell (DC) expression of Nlrp3 is required for IL-18 release in response to the Lm p60 virulence protein. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…AIM2 expression requires type I IFN signalling, consistent with which, L. monocytogenes ‐induced inflammasome activation is severely reduced in type I IFN‐receptor deficient ( Ifnar −/− ) macrophages. L. monocytogenes is a poor activator of NLRC4 (Sauer et al, ; Warren et al, ; Sauer et al, ), but can activate NLRP6, caspase‐11 (Hara et al, ) and NLRP1B (Neiman‐Zenevich et al, ) in mouse macrophages, and NLRP3 in mouse bone‐marrow derived DCs (Clark, Schmidt, McDermott, & Lenz, ). Most L. monocytogenes strains turn down flagellin expression at 37°C and thus evade detection by TLR5 and the NAIP5‐NLRC4 pathway (Theisen & Sauer, ).…”
Section: Monocytogenes Benefits From Inflammasome Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…AIM2 expression requires type I IFN signalling, consistent with which, L. monocytogenes ‐induced inflammasome activation is severely reduced in type I IFN‐receptor deficient ( Ifnar −/− ) macrophages. L. monocytogenes is a poor activator of NLRC4 (Sauer et al, ; Warren et al, ; Sauer et al, ), but can activate NLRP6, caspase‐11 (Hara et al, ) and NLRP1B (Neiman‐Zenevich et al, ) in mouse macrophages, and NLRP3 in mouse bone‐marrow derived DCs (Clark, Schmidt, McDermott, & Lenz, ). Most L. monocytogenes strains turn down flagellin expression at 37°C and thus evade detection by TLR5 and the NAIP5‐NLRC4 pathway (Theisen & Sauer, ).…”
Section: Monocytogenes Benefits From Inflammasome Activationmentioning
confidence: 99%
“…L. monocytogenes is a poor activator of NLRC4 (Sauer et al, 2010;Warren et al, 2010;Sauer et al, 2011), but can activate NLRP6, caspase-11 (Hara et al, 2018) andNLRP1B (Neiman-Zenevich et al, 2017) in mouse macrophages, and NLRP3 in mouse bone-marrow derived DCs (Clark, Schmidt, McDermott, & Lenz, 2018). Most L. monocytogenes strains turn down flagellin expression at 37 C and thus evade detection by TLR5 and the NAIP5-NLRC4 pathway (Theisen & Sauer, 2016).…”
Section: Shigella -Inflammasome Interactions Are Cell-type Specificmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under normal physiological conditions, Batf3 -dependent CD8α + DC appear to play a central role in the activation of CD8 T cells, which has also been corroborated by in vitro studies showing that CD8α + DC are more effective than CD11b + DC at eliciting CD8 T cell responses to Lm [ 26 ]. In addition to their role in transporting Lm to the T cell zone and activating CD8 T cells, a new study demonstrated that Batf3 -dependent CD8α + DC are a vital source of IL-18, which subsequently licenses Natural Killer (NK) cells to produce IL-10 [ 27 ]. As NK cell-derived IL-10 promotes susceptibility to Lm infection [ 28 ], this new study provides an additional mechanism that contributes to the resistance of mice deficient in Batf3 -dependent CD8α + DC to Lm infection.…”
Section: Listeria Monocytogenes (Lm) Acquisitiomentioning
confidence: 99%
“…Infection of wildtype mice with L . monocytogenes results in high levels of serum IL-10 3–4 days post infection [ 11 , 12 ]. Mice lacking IL-10 clear L .…”
Section: Introductionmentioning
confidence: 99%